Ethical, legal and professional issues arising from social media coverage by UK Helicopter Emergency Medical Services. Issue 1 (18th May 2015) - Steele, Sarah; Adcock, Christopher; Steel, Alistair
Abstract : Objective: Social media (SoMe) are gaining increasing acceptance among, and use by, healthcare service deliverers and workers. UK Helicopter Emergency Medical Services (HEMS) use SoMe to deliver service information and to fundraise, among other purposes. This article examines UK HEMS use of SoMe between January and February 2014 to determine the extent of adoption and to highlight trends in use. Methods: The database of the Association of Air Ambulances, crosschecked with UK Emergency Aviation, was used to identify flying, charitable UK HEMS. This search identified 28 UK HEMS, of which 24 services met the criteria for selection for review. Using information harvested from the public domain, we then systematically documented SoMe use by the services. Results: SoMe use by UK HEMS is extensive but not uniform. All selected UK HEMS maintained websites with blogs, as well as Facebook, Twitter, Wikipedia and JustGiving profiles, with the majority of services using Ebay for Charity, LinkedIn and YouTube. Some HEMS also held a presence on Pinterest, Google+, Instagram and Flickr, with a minority of services maintaining their own Rich Site Summary (RSS) feed. Conclusions: The SoMe adopted, while varied, allowed for increased, and different forms of, information delivery by HEMS to the public, often in real time. Such use, though, risks breaching patient confidentiality and data protection requirements, especially when information is viewed cumulatively across platforms. There is an urgent need for the continued development of guidance in this unique setting to protect patients while UK HEMS promote and fundraise for their charitable activities.